2014
DOI: 10.1016/j.jsps.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the use of phosphate binders on serum levels of calcium phosphate in patients with chronic kidney disease undergoing hemodialysis: A retrospective and prospective study

Abstract: We can conclude there are many events happening such as hyperphosphatemia in hemodialysis patients that use phosphate binders. Monitoring of serum levels of calcium phosphate in patients with chronic kidney disease undergoing hemodialysis should be performed every month. Education and the role of clinical staff required to assist compliance and therapeutic efficacy of phosphate binder are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thus, supplementation may be administered to correct this deficiency and avoid hypocalcemia. 14,15 The patient evolved to chemical stomatitis due to inadequate calcium carbonate administration. Many drugs cannot be crushed or have their contents extracted from their capsules due to the risk of complications, including therapeutic failure, drug-nutrient interaction, biological risk due to carcinogenic potential, and damage to the gastrointestinal tract, as noted in this case report.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, supplementation may be administered to correct this deficiency and avoid hypocalcemia. 14,15 The patient evolved to chemical stomatitis due to inadequate calcium carbonate administration. Many drugs cannot be crushed or have their contents extracted from their capsules due to the risk of complications, including therapeutic failure, drug-nutrient interaction, biological risk due to carcinogenic potential, and damage to the gastrointestinal tract, as noted in this case report.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Setiani Agus et al ( 28 ), the majority of patients undergoing hemodialysis developed hypophosphatemia (53.1%) and needed to learn the proper use of their medications, especially phosphorus bonding agents, their significance, and effects of not using their medications. According to the results of Smith et al study ( 29 ), it was found based on the statements of patients that they needed a source for protection and support and to become sensitive to follow the treatment plan and increase their knowledge in this regard ( 29 ).…”
Section: Discussionmentioning
confidence: 99%